PERBANDINGAN PREFERENSI PELAYANAN EKONOMI PENDUDUK RURAL DAN URBAN DI KABUPATEN SLEMAN - Iis Herliany; R. Rijanta; Rini Rachmawati (Fakultas Geografi, Universitas Gadjah Mada, 2009)
ABSTRAK Tulisan ini bertujuan untuk membandingkan karakteristik fasilitas ritel, demografi, sosial ekonomi, dan preferensi fasilitas ritel antara rumah tangga di daerah pedesaan dan perkotaan, serta faktor-faktor yang berhubungan dengan preferensi mereka. Penelitian yang dilakukan di Cangkringan dan Kecamatan Depok sebagai daerah pedesaan dan perkotaan di Kabupaten Sleman. Penelitian ini mengungkapkan bahwa karakteristik fasilitas ritel, sosial-ekonomi rumah tangga dan perilaku dalam pemanfaatan pasar tradisional dan supermarket antara daerah-daerah yang berbeda. Preferensi pasar tradisional berbeda berdasarkan orientasi lokasi pemanfaatan. Preferensi mereka terhadap supermarket juga berbeda berdasarkan tingkat frekuensi pemanfaatan, orientasi lokasi pemanfaatan, dan preferensi faktor daya tarik. Perbedaan-perbedaan terkait dengan karakteristik perilaku sosial-ekonomi, demografi, dan belanja rumah tangga.ABSTRACT This paper is aimed at comparing the characteristic of retail facilities, demographic, socio-economic, and the preference of retail facilities between the households in the rural and urban areas, as well as the factors that correlate with those preferences. The research carried out in Cangkringan and Depok District as the rural and urban area in Sleman Regency. The research reveals thatthe characteristic of retail facilities, household’s socio-economics and behavior in the utilization of traditional market and supermarket between those areas are different. The preference of traditional market is different based on the orientation of the utilization location. Their preferences towards supermarket are also different based on the level of the utilization frequency, the orientation of utilization location, and the preference of attractiveness factors. Those differences are related with the socio-economic, demographic, and shopping behavior characteristic of the households.ABSTRACT This paper is aimed at comparing the characteristic of retail facilities, demographic, socio-economic, and the preference of retail facilities between the households in the rural and urban areas, as well as the factors that correlate with those preferences. The research carried out in Cangkringan and Depok District as the rural and urban area in Sleman Regency. The research reveals thatthe characteristic of retail facilities, household’s socio-economics and behavior in the utilization of traditional market and supermarket between those areas are different. The preference of traditional market is different based on the orientation of the utilization location. Their preferences towards supermarket are also different based on the level of the utilization frequency, the orientation of utilization location, and the preference of attractiveness factors. Those differences are related with the socio-economic, demographic, and shopping behavior characteristic of the households.